2005
DOI: 10.1080/00365520510023666
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio-economic deprivation on outcomes for patients diagnosed with gastric cancer

Abstract: Socio-economic deprivation was associated with younger age at diagnosis, longer diagnostic delay, greater operative mortality and a shorter duration of survival following R0 gastrectomy. These poorer outcomes were not explained by the stage of disease at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…For stomach cancer social gradients were reported for both indicators, but no interpretable differences in case fatalities emerged. This finding is not in accordance with other European studies where excess mortalities were reported for lower socioeconomic groups [47], although group differences were sometimes small [48]. Incidences and case fatalities of stomach cancer were declining over the past decades [49].…”
Section: Discussionmentioning
confidence: 41%
“…For stomach cancer social gradients were reported for both indicators, but no interpretable differences in case fatalities emerged. This finding is not in accordance with other European studies where excess mortalities were reported for lower socioeconomic groups [47], although group differences were sometimes small [48]. Incidences and case fatalities of stomach cancer were declining over the past decades [49].…”
Section: Discussionmentioning
confidence: 41%
“…Further prospective studies are, therefore, needed not only to evaluate this aspect but would undoubtedly contribute to reaching a more accurate evaluation of symptoms and their impact on prognosis. Symptoms may vary from the onset to the diagnosis and referral of symptoms may depend on social and cultural factors [71] . A supportive study, in this direction carried out by Meineche-Schmidt and Jørgensen [17] in a primary care setting revealed that the majority of patients in whom upper gastro-intestinal cancer developed did not have alarm symptoms at their initial primary care consultation.…”
Section: Duration Of Symptoms and Outcome Of Gastric Cancermentioning
confidence: 99%
“…Esta situación, en otras regiones del mundo, también se ha evidenciado. Un estudio del Reino Unido de 2005 evalúo la deprivación socioeconómica (mediante el Index of Multiple Deprivation -IMD-) frente a los resultados de pacientes con cáncer de estómago, identificando en las poblaciones menos favorecidas que la supervivencia a 5 años era del 32%, frente al 66% de los más favorecidos y la mortalidad operatoria era tres veces mayor [18]. Adicionalmente, es reconocido a nivel mundial que la tasa de letalidad es más baja en países con más altos niveles de desarrollo humano [19].…”
Section: Discussionunclassified